Blockchain Empowers Chain Enterprises in the Digital Economy to Strengthen Risk Management Research - Weiwei Su (Journal of Electrical and Computer Engineering)
With the vigorous development of blockchain technology, researches on various “blockchain+” scenarios continue to bring forth new ideas. As some of the characteristics of the blockchain technology itself deeply meet the demands of the development of chain enterprises, it can better control the related risks of enterprises. Therefore, it is necessary to combine the characteristics of blockchain technology with the characteristics of chain enterprise risks and the interaction mechanism for research. This article aims to study how to strengthen risk management for chain enterprises in the digital economy. For this reason, this article proposes a method to empower the digital economy through the blockchain and calculates and analyzes the risk measurement so that it can effectively estimate the risk. This article also designs an experimental analysis to explore its effect. The experimental results of this paper show that after the improvement, the risk of chain enterprises is reduced by 35%, and the risk is effectively controlled.